PENGARUH MODEL WEBBED TEMA ENERGI TERHADAP HASIL BELAJAR SISWA KELAS VII SMPN 1 KETAPANG - Anggraheni, Lidia; Enawaty, Eny; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aimed of this study were to determine whether there was significant difference of achievement between students who are taught through Webbed Model of Integrated Natural Science Learning and Conventional Learning and to determine the effect of Webbed Model of Integrated Natural Science Learning on the theme of Energy in Life System towards students achievement. Pretest and posttest control group design was adopted as research design. Two sample were selected randomly nine classes at seven grade of SMPN 1 Ketapang. They were VII A class as control group and VII D class as experimental group. Expermental group was taught through Webbed Model of Integrated Natural Science Learning. Meanwhile, control group was taught through Conventional Learning. According to data analysis, probability score was 0.029. It was smaller than 0.05 which meant there was a significant difference between both classes. According to calculation of Effect Size, the score of effect size was 0.5 which was categorized as medium. In conclusion, there was a significant difference of achievement between students who are taught through Webbed Model of Integrated Natural Science Learning and Conventional Learning and the effect of Webbed Model of Integrated Natural Science Learning is medium towards students achievement.Keywords: Energy, Students Achievement, Webbed Model